2011
DOI: 10.2478/v10153-010-0022-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Physical Activity and Eating Behaviour with Obesity and Type 2 Diabetes Mellitus: Sofia Lifestyle (SLS) Study

Abstract: We found a strong inverse relationship between the level of PA during leisure time (including sport), BMI, and the prevalence of T2DM. Uncontrolled eating behaviour was also found to have a significant effect on BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
4
12
0
Order By: Relevance
“…Previous research has shown that physical inactivity plays a major role in the etiology of both T2D and obesity. BMI was negatively correlated with physical activity in our study population (data not shown), in accordance with previous studies [34, 37, 38]. Possible explanations for the role of physical activity as an effect modifier in this research may be that physical activity increases sensitivity to insulin [39], and can result in weight loss [40].…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown that physical inactivity plays a major role in the etiology of both T2D and obesity. BMI was negatively correlated with physical activity in our study population (data not shown), in accordance with previous studies [34, 37, 38]. Possible explanations for the role of physical activity as an effect modifier in this research may be that physical activity increases sensitivity to insulin [39], and can result in weight loss [40].…”
Section: Discussionsupporting
confidence: 91%
“…At the same time a healthier lifestyle comprising higher levels of PA and prudent food consumption have been found to signifi cantly reduce the risk ( Coakley et al, 1998 ;Kriska et al, 2003 ;Meisinger et al, 2005 ;Schulze et al, 2006 ;van Dam et al, 2002 ). In a recent paper we reported that low levels of leisure time and sport PA, as well as, binge eating behavior are associated with increased BMI and higher T2DM prevalence also among the urban population of Sofi a, Bulgaria ( Stefanov et al, 2011 ). Based on data analyses from the Nurses' Health Study Hu et al (2003a) concluded that around 30 % of the new cases of obesity and 43 % of T2DM could be prevented by adoption of a relatively active lifestyle.…”
Section: Lessons From Epidemiological Studiesmentioning
confidence: 82%
“…Here, we found a first example of a molecular signal foul-up between motor hyperactivity and anorexia, providing a common pathway of control. This would lead us to reconsider the belief that patients with anorexia nervosa intend to accelerate their weight loss with over-exercise 3, 31, 32, 33 because hyperactivity could be more inevitable than deliberate.…”
Section: Discussionmentioning
confidence: 99%